OBSTACLES IN THE INTEGRATION OF TECHNOLOGY IN LEARNING AT MADRASAH IBTIDAIYAH NURUL ULUM - Arif, Muhammad; Atus Soliha, Imro; Khosiah, Nur (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
The combination of information and communication technology in the teaching and learning process at Madrasah Ibtidaiyah is still constrained by various structural aspects and limited resources. Based on research at MI Nurul Ulum, the most significant obstacle lies in the availability of facilities in a number of classrooms that are not equipped with projectors, adequate computers, and stable internet access—so that digital learning practices cannot be carried out evenly. In addition, most teachers have not mastered the use of educational software and supporting digital media, so the effectiveness of the use of technology in the classroom is still not optimal. The lack of firmness in the internal policies of madrasas to support ICT integration further weakens these efforts; Existing directives are often only recommendations without clear evaluation mechanisms, incentives, or sanctions. The pedagogical aspect is also a challenge in itself, where educators are not fully ready to design and implement learning that combines technology with the nuances of Islamic values, because conceptual understanding and digital-based pedagogical skills are still limited. Similar findings in the literature confirm that the readiness of teachers as a whole is the key to the success of the use of technology in religious education, so that the shortcomings in this case are the main inhibiting factors. Therefore, integrated efforts are needed, ranging from improving ICT infrastructure and providing continuous training for teachers to rearranging madrasah policies that are more proactive in facilitating learning innovation. With a holistic strategy and full support from various stakeholders, the integration of information and communication technology at MI Nurul Ulum is expected to run more effectively and sustainably